Stomatal response of some cultivated and wild tuberbearing potatoes in warm tropics as influenced by water deficit stress - Ekanayake, I.J.; Jong, J.P. de (Oxford University Press, 1992)
Leaf resistances of 14 cultivated potato genotypes ( Solanum spp.) and three tuber-bearing wild Solanum species were compared when plants were grown under water stress at two tropical sites. Factors investigated were diurnal changes in leaf resistance, the effect of plant age, transient drought versus well-watered conditions of potted and field-grown plants. These measurements were carried out in order to determine the stomatal behaviour of tuber-bearing genotypes and species. Significant genotypic differences in leaf resistances were noted within the cultivated genotypes. All genotypes had higher resistances when water-stressed, but LT-7 appeared to have the lowest leaf resistances. Genetic differences in stomatal behaviour of tuber-bearing Solanum species were confirmed. Abaxial stomatal resistances of water-stressed plants of the species ranged between 1-74 and 13-8 s cm-1. Stornata of S. chacoense were less affected by drought (three-fold) than S. tuberosum (four-fold). The greatest effect was on S. júngaseme (five-fold) and on S. raphanifolium. These data show that stornata behaviour among tuber-bearing Solanum species is sufficiently different to warrant investigations of drought-resistance in potato species under dry hot conditions.